DAMPAK PERILAKU EKSPLOITASI TERHADAP EFISIENSI DAN TINGKAT KEHIDUPAN PETANI PLASMA PIR-SUS KELAPA SAWIT - Imam Asngari (Jurnal Ekonomi Pembangunan, 2006)
The purpose of this study are to analyze conduct on exploitation by Nucleus Estate as a monopsonist, self-exploitation mechanism by farmers and does to impact on efficiency and farmer's quality of live. Research sampling is taken by using stratified random sampling method on NES [Nucleus Estate and Smallholders] at Muara Enim Municipality in South Sumatera Province. Sample of farmers selected by using stratified production random sampling. The quantitative and qualitative descriptive analyze is also applied in this study through measuring value added,   efficiency, production surplus, exploitation,  and farmer's quality of live. The result of this research sow that exploitation by NES conduct is characterized  by mark-up input prices, reduce to TBS output prices, and to bring down conduct on farmer's institution. The NES system has made farmers to fall under exploitation mechanism by NES, banks, farmer's institution and self-exploitation system. In this way exploitation has to be institution in the contract farming in the NES system. The exploitation system has impact on decrease welfare and farmer's efficient, loss production surplus, low productivity and affected on leveling up in the poverty. Keywords: NES System,  production surplus, exploitation mechanism, self-exploitation, farmer's efficient and poverty.